(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, the image of a leaf, which is an active and traditional symbol, is analyzed in the lyrics of Rauf Parfi, a mature representative of Uzbek poetry of the independence period. The artist reveals society and his situation, as well as the image of living nature, in the spirit of artistry through the image of a leaf. The symbol of the leaf is expressed in its new meanings every time in the artist’s lyrics.